High Virologic Failure Rates with Maraviroc-Based Salvage Regimens Among Indian Patients: A Preliminary Analysis—Maraviroc Effectiveness in HIV-1 Subtype C. (22nd February 2018) - Pujari, Sanjay; Gaikwad, Sunil; Bele, Vivek; Joshi, Kedar; Dabhade, Digamber
Background: There is no information on the clinical effectiveness of Maraviroc (MVC) amongst People Living with HIV (PLHIV) in India infected with HIV-1 Subtype C viruses. Methods: We conducted a retrospective chart review of adult PLHIV on MVC based Antiretroviral (ARV) regimens for at least 6 months. Maraviroc was initiated amongst PLHIV with documented R5 tropic viruses (determined by in-house population sequencing of the V3 loop in triplicate and interpreted using the Geno2Pheno algorithm) in combination with an Optimized Background regimen (designed using genotypic resistance testing and past ARV history). Plasma viral loads (PVL) are performed 6 months post-initiation and annually thereafter. Primary outcome d. Median duration on MVC treatment was 1.8 years (range 1-2.9 years) while median duration of ART prior to switching to MVC was 13 years. Maraviroc was combined with Darunavir/ritonavir (DRV/r) (n=10), Atazanavir/r (ATV/r) (n=2) and Lopinavir/r (LPV/r) (n=1). All PLHIV were infected with HIV-1 Subtype C. Only 23.3% PLHIV achieved virologic suppression at 6 months and sustained it for 2.3 years. Median CD4 count change from baseline was +117 (n=13), +228 (n=10), +253 (n=9), and +331 (n=4) at 6, 12, 18 and 24 months respectively. Repeat tropism among patients with virologic failure demonstrated R5 virus. Conclusions: High rates of virologic failure was seen when MVC was used amongst treatment experienced PLHIV infected with HIV-1 Subtype C in India. was the proportion of PLHIV with virologic success (PVL<50 copies/ml) at last follow up visit. Results: Data on 13 PLHIV were analyze